CaMKIIγ regulates the viability and self‐renewal of acute myeloid leukaemia stem‐like cells by the Alox5/NF‐κB pathway. (25th December 2020) - Cheng, Jiang‐Hua; Zhang, Wen‐Jing; Zhu, Jun‐Feng; Cui, Di; Song, Kai‐Di; Qiang, Ping; Mei, Chuan‐Zhong; Nie, Zheng‐Chao; Ding, Bang‐Sheng; Han, Zhong; Ding, Zhi‐En; Zheng, Wei‐Wei
Abstract: Acute myeloid leukaemia (AML) is a frequently fatal malignant disease of haematopoietic stem and progenitor cells. The molecular and phenotypic characteristics of AML are highly heterogeneous. Our previous study concluded that CaMKIIγ was the trigger of chronic myeloid leukaemia progression from the chronic phase to blast crisis, but how CaMKIIγ influences AML stem‐like cells remains elusive. In this study, we found that CaMKIIγ was overexpressed in AML patients and AML cell lines, as measured by qRT‐PCR and Western blot assays. Moreover, CaMKIIγ decreased when the disease was in remission. Using an shRNA lentivirus expression system, we established CaMKIIγ stable‐knockdown AML cell lines and found that knockdown of CaMKIIγ inhibited the viability and self‐renewal of AML stem‐like cell lines. Additionally, the ratio of CD34 + AML cell lines decreased, and CaMKIIγ knockdown induced the downregulation of Alox5 levels. We further detected downstream molecules of the Alox5/NF‐κB pathway and found that c‐myc and p‐IκBα decreased while total IκBα remained normal. In conclusion, our study describes a new role for CaMKIIγ as a stem‐like cell marker that is highly regulated by the Alox5/NF‐κB pathway in AML stem‐like cells. CaMKIIγ can participate in the viability and self‐renewal of AML stem‐like cells by regulating the Alox5/NF‐κB pathway.